2019
DOI: 10.1039/c9sc02012h
|View full text |Cite
|
Sign up to set email alerts
|

Construction and interconversion of anion-coordination-based (‘aniono’) grids and double helicates modulated by counter-cations

Abstract: ‘Aniono’ double helicates and grids were constructed using PO43− anions and a bis–tris(urea) ligand and interconverted by changing the counter-cation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 75 publications
0
27
0
Order By: Relevance
“…Encouraged by our previous work, 45 we aim to further explore the predictable geometry of anion-coordinated complexes for the programmable construction of new topologies from the tris(urea) building block, which has displayed strong coordination affinity to phosphate. By examining the single crystal structures of our previously reported tris(urea) complexes, 44,45 we observed angles between the linkers and PO 4 3− ranging from 73.7°to…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Encouraged by our previous work, 45 we aim to further explore the predictable geometry of anion-coordinated complexes for the programmable construction of new topologies from the tris(urea) building block, which has displayed strong coordination affinity to phosphate. By examining the single crystal structures of our previously reported tris(urea) complexes, 44,45 we observed angles between the linkers and PO 4 3− ranging from 73.7°to…”
Section: Introductionmentioning
confidence: 90%
“…Even though the construction of well-defined supramlecular architectures utilizing anion-coordination-driven assembly (ACDA) has so far not been as extensively studied as conventional metal-coordination, [33][34][35][36][37][38][39] studies on the assembly of oligo-urea ligands and anions have demonstrated that the coordination behavior of the phosphate anion is analogous to that of octahedral transition metals. [40][41][42][43][44] This tetrahedron-shaped phosphate anion (PO 4 3− ) can readily form both AL 3 complexes with the "bidentate" bis(urea) moiety and AL 2 fragment with the "tridentate" tris(urea) coordination sites. 44,45 However, while successful assembly of a series of anionic architectures based on bis(urea) moieties and phosphate (through the AL 3 coordination motif) has been achieved, only one discrete A 4 L 4 (A = anion) square-shaped macrocycle constructed from tris(urea) and phosphate anions (through the AL 2 motif) has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have developed a new strategy, anion‐coordination‐driven assembly (ACDA), for construction of discrete supramolecules, and various well‐defined structures, [20] including tetrahedral cages, [21] grids, [22] triple‐ [23] and double helicates, [22] and prisms, [24] have been obtained. For the A 2 L 3 triple helicates composed of two phosphate anions and three bis‐bis(urea) ligands, it is found that proper spacer (that connects the two bis(urea) arms) of the ligand can create a central cavity capable of guest binding [23b] .…”
Section: Figurementioning
confidence: 99%
“…[16][17][18][19] Although the most traditional helices were designed in the context of the secondary structure, higherorder structures containing multiple helices should be considered to establish superior functions as seen in biomolecular systems. [20][21][22][23][24][25] Precise construction of the higher structures containing the artificial helices has been studied by using reversible processes such as metal complexations, [26][27][28] noncovalent interactions, [29][30][31][32][33] and dynamic covalent bonds. [34][35][36][37][38] The repetitive formation and deformation of bonds and attractive interaction by those approaches gradually lead reaction mixtures to thermally stable higher-order structures.…”
Section: Introductionmentioning
confidence: 99%